The Role of the Catholic Church in the 1994 Genocide in Rwanda - I. U. Khatagova (Концепт: философия, религия, культура, 2023)
Studies in the sphere of history and culture of the African continent attract an increasing interest given the ongoing development of African countries, the reinforcement of ties with Russia as well as the erosion of stereotypes about the nations that populate these territories. This article suggests that the Catholic Church played a significant role in the formation of the Rwandese society in 1890–1994, with the genocide of 1994 being one of the central events. In the framework of the study, the author seeks to reveal the background of the genocide that became the culmination of long-lasting contradictions between Hutu and Tutsi in Rwandan society. One of the main goals of the research was to investigate how the terms Hutu and Tutsi were transformed from social to quasi-ethnic ones. Special attention in this regard was paid to the role of the Catholic Church in the destruction of Rwandan collective self-identification, the growth of tribalism, and antagonism within the society. The article employs the methods of content analysis, case study, event analysis, discourse analysis and interview to research the official position of the Catholic Church during the genocide as well as the actions of specific priests, which is crucial for understanding the controversial role of the Church in the tragedy. Starting from the colonial period the Catholic Church had a vast influence not only in the spiritual but also in the social sphere, including education and mass media. Analyzing the empowerment of the Hutu in Rwanda, in general and especially within the Catholic Church in the country, the author traces back the evolution of social relations in the second half of the 20th century in order to help understand the particular historical role of the Church in the country and in relations between the Hutu and Tutsi along with their quest for power. The author concludes that one of the most interesting issues is the merging of the church’s elite and radical political leadership of Rwanda, which resulted in the further degradation of social relations in the country, growing mutual tensions between Hutu and Tutsi and, in the long run, the genocide. The post genocide analysis of the Catholic Church’s politics reveals not only tools used by the institute to facilitate national reconciliation but also the measure of responsibility for the genocide that it has agreed to take.